Assessment of the potential risks in SD rats gavaged with genetically modified yeast containing the cp4-epsps gene - Bo Bi; Bo Bi; Xuewei Fu; Xuewen Jian; Yu Zhang; Yizhi Jiang; Wuyi Zhou; Hui Zhao (Frontiers in Veterinary Science, 2024)
IntroductionDespite the absence of definitive evidence indicating that the cp4-epsps gene and its resultant recombinant proteins have significant harmful effects on either human or animal health, the safety assessment of genetically modified (GM) crops expressing the CP4-EPSPS proteins has been controversial. This study endeavor was aimed at evaluating the potential risks posed by the CP4-EPSPS protein in transgenic crops, thereby contributing to the advancement of risk assessment methodologies in the context of genetically engineered crops.MethodsTo ascertain the appropriate daily dosages for oral gavage administration, the expression levels of the CP4-EPSPS protein in a recombinant yeast were quantified. Subsequently, physiological and biochemical analysis, metabolomics, and metagenomic analysis were conducted based on a 90-day Sprague-Dawley (SD) rats feeding experiment, respectively, thereby enhancing the depth and precision of our risk assessment framework.ResultsThe results from the physiological and biochemical analysis, organ pathological, blood metabolism, gut microbiota, and correlation analysis of metabolites and gut microbiota revealed several biomarkers for further risk assessment. These biomarkers include clinical biochemical indexes such as total bilirubin (TBIL), direct bilirubin (DBIL), creatine kinase (CK), and lactate dehydrogenase (LDH); metabolites like Methionine, 2-Oxovaleric acid, and LysoPC (16:0); and gut microbiota including Blautia wexlerae, Holdemanella biformis, Dorea sp. CAG 317, Coriobacteriaceae and Erysipelotrichaceae.ConclusionIn conclusion, the risk can be significantly reduced by directly consuming inactivated recombinant CP4-EPSPS. Therefore, in everyday life, the risk associated with consuming GM foods containing recombinant CP4-EPSPS is substantially reduced after heat treatment.